PELATIHAN BAHASA INGGRIS BEREKUIVALENSI TOEFL (Test English as a Foreign Language) BAGI GURU SMK MUHAMMADIYAH 2 RAWA BENING OKU TIMUR - Eka Marwati, Hastuti Retno Kuspiyah, Ainur Rohmah & (Widya Wacana: Jurnal Ilmiah, 2016)
The objective of this program are: 1) to apply the training of English that equivalenceTOEFL in increasing the teachers’ English skill at SMK Muhammadiyah 2 Rawabening OKUTimur. 2) to give the learning experience of English for the teachers at SMK Muhammadiyah 2Rawabening OKU Timur. Whereas the participant of this program is the teachers of SMKMuhammadiyah 2 Rawabening OKU Timur, consisted of 17 people. The process of this programare by introduced between school board and the team of the program from STKIP Nurul HudaSukaraja, after that recognized the materials to the participants. And gave pretest to know theteachers’ skill before training and then did training around two weeks. Meanwhile, the materialsdevided into three basic skills, they are: Listening, Structure and Written Expression, andReading Comprehension. After finishing the process for the teachers gave the posttest toinvestigate whether or not there will be increasing result when it is compared to the result gainedby the teachers in pretest. Based on the result of this program, there are some significances,namely: 1) it can measure the teachers’ English skill at SMK Muhammadiyah 2 RawabeningOKU Timur. 2) it is as a motivation in increasing the teachers’ English skill at SMKMuhammadiyah 2 Rawabening OKU Timur.Key Words: 1) English , 2) Equivalence, and 3) TOEFL